Crystal structure of 1-(1-chloroethyl)-6,7-dimethoxy-1,2,3,4-tetrahydroisoquinolinium chloride - Ziroat E. Urunbaeva; Kambarali K. Turgunov; Abdusalom Sh. Saidov; Valentina I. Vinogradova (Acta Crystallographica Section E: Crystallographic Communications)
1-(1-Chloroethyl)-6,7-dimethoxy-1,2,3,4-tetrahydroisoquinoline was synthesized through the reaction of homoveratrylamine with racemic lactic acid. The formation of two enantiomers, RR and SS, was detected by performing X-ray diffraction analysis on their chloride salts. The asymmetric unit of the crystal consists of a C13H19ClNO2+ molecular cation and a Cl− anion. Two protonated enantiomers of the title compound, with RR and SS configurations of the chiral atoms, are connected into hydrogen-bonded dimers bridged by Cl− anions. Weak C—H...Cl interactions lead to the formation of a chain running along the a-axis direction of the unit cell, which corresponds to the longest dimension (the preferential growth direction) of the needle-shaped monocrystal. The crystal studied was refined as a two-component twin.